ANALISIS FILOSOFIS TERHADAP PERAN HEREDITAS, LINGKUNGAN, KEBEBASAN MANUSIA, DAN HIDAYAH ALLAH DALAM MEMBENTUK KARAKTER ISLAMI - Firmansyah Firman; Nur Afifah (Taskuliah Edukasi Indonesia, 2026)
Human behavior is complex and can easily be influenced by various factors, including heredity, environment, human freedom, and belief in the existence of guidance from Allah.This research aims to analyze the role of heredity, environment, human freedom, and Allah guidance in shaping Islamic character. This research uses a